Population structure of swap eel Monopterus albus in east coast of peninsular Malaysia inferred from mitochondrial dna analysis - Ahmad Syazni, K.; Norshida, I.; Komilus, C.F.; Chew, H.H.; Ing, N.S. (2016)
Swamp eel Monopterus a/bus is a highly commercial food fish with medicinal value in Malaysia, where the East Coast Peninsular Malaysia (ECPM) is the second largest contributor of swamp eel's annual production. The reduction of wild stocks due to overfishing has encouraged the breeding and culturing of this species. A better understanding of its population structure will aid the breeders to determine how to exploit these natural gene resources effectively as brood stock in the hatchery . A total of 61 samples were collected at six different sampling sites from Kelantan, Terengganu and Pahang to investigate the baseline data on the fundamental population genetics structure of the swamp eel in ECPM. The partial mtDNA l6s rRNA gene detected four haplotypes among all the samples. Haplotype-1 was the most widespread haplotype among the six sampling sites, comprising of 75.4% of all samples. Both non-significant values of Tajima's D and Fu's Fs suggested that all populations were at genetic equilibrium. Analysis of Molecular Variance (AMOVA) revealed a significant differences among sampling sites ( Fs1 = 0.924, P < 0.05). In pairwise comparisons of Fsr, population of swamp eel i n Kuala Terengganu showed significant values (P < 0.05) among all populations. The non-significant values of Fsr showed that Pasir Puteh. Tanah Merah, Rantau Panjang, Kampung Raja and Pekan are less genetically different and closely related population. This suggests that the swamp eel in Kuala Terengganu may be genetically differentiated population compared to the other sampling sites in ECPM.